PARANOIA IN THE GENERAL POPULATION: A REVISED VERSION OF THE GENERAL PARANOIA SCALE FOR ADOLESCENTS - Carvalho, Celia Barreto; Pereira, Vera; Sousa, Marina; da Motta, Carolina; Pinto-Gouveia, Jose; Caldeira, Suzana Nunes; Peixoto, Ermelindo Bernardo; Fenigstein, Allan (European Scientific Journal, ESJ, 2014)
The aim of the current study was to validate the General Paranoia Scale for Portuguese Adolescents population (GPS-A). This scale assesses the paranoid ideation in non-clinical population. Results from a confirmatory factor analysis of the scale on 1218 youths confirmed an alternative model to the one-dimensional model proposed by Fenigstein and Vanable (1992) comprising three different dimensions (Mistrust thoughts, persecutory ideas and depreciation). This alternative model presented a good fit: χ2 (162)= 727.200, p = .000; CFI = .925; RMSEA = .054, P(rmsea ≤0.05) = .000; PCFI = .788; AIC = 863.200. All items presented adequate factor loadings (λij ≥0.5) and individual reliability ((λij)2 ≥0.25). Further data analysis on the scale revealed that the GPS-A is an adequate assessment tool for adolescents, with good psychometric characteristics and high internal consistency.